2015
DOI: 10.1530/erc-15-0134
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase sequence variants may predispose to prostate cancer

Abstract: We hypothesized that mutations that inactivate phosphodiesterase (PDE) activity and lead to increased cyclic AMP (cAMP) and cyclic GMP (cGMP) levels may be associated with prostate cancer (PCa). We sequenced the entire PDE coding sequences in the DNA of 16 biopsy samples from PCa patients. Novel mutations were confirmed in the somatic or germline state by Sanger sequencing. Data were then compared to the 1000 Genome Project. PDE, CREB and pCREB protein expression was also studied in all samples, in both normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“… have reported that PDE10A mutations are predicted to influence PDE10A allosteric regulation in lung adenocarcinoma; that high levels of PDE10A expression correlate with worsened lung adenocarcinoma prognosis; and that Pf‐2545920 also suppresses the growth of NSCLC cell lines. Finally, PDE10A somatic mutations have been described in up to 19% of prostate cancers and correlated with increased levels of phosphorylated C‐AMP responsive element binding protein (p‐CREB) . These data suggest that PDE10A might be a relevant target for cancer therapy and prevention.…”
Section: Discussionmentioning
confidence: 97%
“… have reported that PDE10A mutations are predicted to influence PDE10A allosteric regulation in lung adenocarcinoma; that high levels of PDE10A expression correlate with worsened lung adenocarcinoma prognosis; and that Pf‐2545920 also suppresses the growth of NSCLC cell lines. Finally, PDE10A somatic mutations have been described in up to 19% of prostate cancers and correlated with increased levels of phosphorylated C‐AMP responsive element binding protein (p‐CREB) . These data suggest that PDE10A might be a relevant target for cancer therapy and prevention.…”
Section: Discussionmentioning
confidence: 97%
“…A high frequency of PDE variants was observed in patients with prostate cancer [31]. The pCREB:CREB ratio (phosphorylated cAMP response element-binding protein: cAMP response elementbinding protein) showed an imbalance in the cAMP availability, probably due to downregulation of some of the PDE molecules [31].…”
Section: Discussionmentioning
confidence: 99%
“…A high frequency of PDE variants was observed in patients with prostate cancer [31]. The pCREB:CREB ratio (phosphorylated cAMP response element-binding protein: cAMP response elementbinding protein) showed an imbalance in the cAMP availability, probably due to downregulation of some of the PDE molecules [31]. In the present work, when the transcriptome analysis was accessed, a decrease of PDE2A, PDE5A, and PDE8A expression and a significant overexpression of PDE4B and PDE8B was observed in adrenocortical tumors, compared to normal adrenal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in cancer is context dependent, as the cellular effect of a cAMP signal depends on the cell type and subcellular localization of the signal [ 36 , 38 ]. In the select cases in which cAMP has been shown to be oncogenic [ 39 ], it may act directly on protein kinase A (PKA) or indirectly on its downstream effectors, cAMP-responsive element binding protein and Rap Guanine Nucleotide Exchange Factor 3 (RAPGEF3) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%